Research hotspots and frontiers of post-stroke aphasia rehabilitation: a bibliometric study and visualization analysis - Wang, Huan; Cai, Ziping; Li, Shengjuan; Zheng, Jiaxing; Xie, Yuyao; He, Yuanyuan; Li, Chen; Zheng, Dongxiang (Frontiers in Human Neuroscience, 2023)
Background: Aphasia is a common complication of stroke and is associated with high morbidity and mortality rates. Rehabilitation plays a crucial role in the comprehensive management of poststroke aphasia and its consequences. However, bibliometric analysis in the field of poststroke aphasia rehabilitation is still lacking. This study aimed to comprehensively identify assistance networks, analyze research trends, focus on hot and cutting-edge health topics related to poststroke aphasia rehabilitation, and inform future research guidelines. Method: The Web of Science Core Collection (WoSCC) electronic database was searched from inception to January 4, 2023 to identify studies related to poststroke aphasia rehabilitation. Bibliometric analysis and visualization of country, institution, journal, author, reference, and keywords were performed using CiteSpace and VOSviewer software. Results: A total of 2,325 papers were included in the analysis, with a progressive increase in the number of articles published each year. The USA was the country with the most publications (809 articles), and the University of Queensland was the institution with the most publications (137 articles). The subject area of poststroke aphasia rehabilitation is dominated by clinical neurology (882 articles). Aphasiology was the journal with the most publications (254 articles) and the most cited journal (6,893 citations). Worrall L was the most prolific author (51 publications), and Frideriksson J was the most cited author (804 citations). Conclusions: By using bibliometrics, we provided a comprehensive review of studies related to poststroke aphasia rehabilitation. Future research hotspots on topics related to poststroke aphasia rehabilitation will mainly focus on the plasticity mechanisms of neurolinguistic networks, language function assessment, language rehabilitation modalities, and patients' rehabilitation needs and participation experiences in poststroke aphasia. This paper provides systematic information that is worth exploring in the future.